Chapter Il progetto SEPA360 nella percezione degli studenti - Cuomo, Stefano (Studi e saggi, 2022)
This chapter focuses on the perception of the students about the video 360° and their didactic value in the academic teaching. The results of an online survey, administered to more than 200 students in three European countries who followed an academic course where a video 360° was used, are then presented and discussed highlighting how, despite the relative novelty of this tool for academic teaching, the results seem quite promising for their further adoption in the Higher Education.